Once Again on the Question of the Headlines of the “New Media” as an Object of Pragmatics and Media Ecology - Kazimianec, Jelena (Slavistica Vilnensis, 2020)
The article continues the analysis of the problem previously raised by the author, which deals with the nature of the headlines of modern new media. This article presents a pragmatic perspective on the study of headings aimed at attracting the attention of readers from the point of view of their correspondence to the postulates of communication of J. Grice. The article shows that the attention of the reader is often attracted by the violation of such cooperative principles as the postulate of quantity (maxim of quantity). The author focuses on the speed of dissemination of information under a certain heading and notes the transformation of headlines on various news sites. This makes it possible to assess the place of a news site in the media space and to determine how correctly the news resource uses the information received from another resource. The article attempts to establish a correlation between the “viral” headlines and the nature of modern culture that affects the reasons for their creation and transformation. Following the concept of media education of the English theorist of culture and media education L. Masterman, the author outlines possible ways of developing critical thinking on the basis of such headings, which are an integral part of the “new media”.
Keywords: media linguistics; “new media”; title (headline); clickbait; communication postulates; reduction of meaning and form; mass culture; media education